Nanostructured Lipid Carriers Aimed to the Ocular Delivery of Mangiferin: In Vitro Evidence - Debora Santonocito; Ignazio Barbagallo; Alfio Distefano; Giuseppe Sferrazzo; Maria Vivero-Lopez; Maria Grazia Sarpietro; Carmelo Puglia (MDPI AG, 2023)
Although mangiferin (MGN) is a natural antioxidant that could be a good candidate for the treatment of ocular diseases, its use in ophthalmology is strongly compromised due to its high lipophilicity. Its encapsulation in nanostructured lipid carriers (NLC) seems to be an interesting strategy for improving its ocular bioavailability. As reported in our previous work, MGN-NLC showed high ocular compatibility and fulfilled the nanotechnological requirements needed for ocular delivery. The aim of the present work was to investigate, in vitro and ex vivo, the capability of MGN-NLC to act as a potential drug delivery system for MGN ocular administration. The data obtained in vitro on arising retinal pigment epithelium cells (ARPE-19) did not show cytotoxic effects for blank NLC and MGN-NLC; likewise, MGN-NLC showed the maintenance of the antioxidant role of MGN by mitigating ROS (Reactive Oxygen Species) formation and GSH (glutathione) depletion induced by H2O2. In addition, the capacity of MGN-released to permeate through and accumulate into the ocular tissues was confirmed ex vivo using bovine corneas. Finally, the NLC suspension has been formulated as a freeze-dried powder using mannitol at a concentration of 3% (w/v) in order to optimize its storage for long periods of time. All this evidence suggests a potential application of MGN-NLC in the treatment of oxidative stress-related ocular diseases.